The Effect of Ladder Drill Training on Speed and Agility Improvement in Junior Badminton Athletes Aged 11-14 Years - Khanina, Naila; Hazar, Fatih; Damayanti, Enarnimas; Bayu, Sani (Journal of Racket Sports Performance & Science (JRSPS), 2025)
Background: This study aims to determine the effect of ladder drill training on improving speed and agility in badminton athletes aged 11-14 years. This age is considered the golden period of motor development, so training intervention at this age is expected to provide optimal results. Research Objectives: To determine the effect of ladder drill training on improving speed and agility in badminton athletes aged 11-14 years. Methods: The research method used was a quasi-experiment with a pre-test and post-test control design. The sample consisted of 30 junior athletes (12 males, 18 females) with an average age of 12.6 ± 1.1 years from a badminton club. Participants were randomly divided into an Experimental Group (LDT, n=15) who received 20 minutes of ladder drill training, 3 times a week for 8 weeks, and a Control Group (CG, n=15) who only underwent regular training. Speed was measured using a 20-meter sprint test, while agility was measured using a T-test. Data analysis used Paired t-tests and Independent t-tests with a significance level of p < 0.05. Result: The Experimental Group experienced a significant increase in speed with an average time reduction of 0.28 seconds (p=0.001) and agility with an average time reduction of 0.72 seconds (p=0.000). The Control Group did not show significant changes (p > 0.05). Conclusion: Ladder drills are very effective in improving speed and agility in badminton players aged 11-14 years.